Short-term skin reactions and changes in stratum corneum following different ways of facial sheet mask usage - Wang, Yixin; Cao, Yuegang; Huang, Xiaodong; Zhang, Mu; Hu, JiaFeng; Li, Li; Xiong, Lidan (Journal of tissue viability, 2024)
The global facial mask market grows steadily at 8.5 % annually. However, prolonged use may lead to skin inflammation. To investigate how various mask types and wearing durations impact skin physiology and aquaporins3 (AQP3) expression in healthy subjects. We used a randomized controlled design to investigate the effects of three types of facial masks (pure water, hyaluronan, and bifida ferment lysate) and four different duration(5, 15, 25, and 40 min) on various skin parameters in volunteers, assessing moisture content, transepidermal water loss (TEWL), sebum, corneocyte size, and AQP3 expression before and after mask application, while also evaluating adverse reactions, discomfort, and noncompliance. Hydration and TEWL increased at first, then decreased. Sebum increased with all types of masks, particularly after 40 min. Vasodilation and AQP3 expression were linked to mask duration. Corneocyte sizes remained constant. The main adverse reactions were redness (10.71 %, n = 28) and dryness (57.14 %, n = 28), especially with pure water masks lasting over 25 min. Short-term use of facial sheet masks (<25 min) benefits skin with improved hydration, reduced redness, and AQP3 activation, while prolonged use can lead to increased dryness and redness. •Both benefits and drawbacks of facial masks were noted, with references for the recommended duration of daily use.•AQP3 activation in keratinocytes may affect stratum corneum permeability and moisture retention in clinical tarils, serving as a potential indicator for future hydration prognostication.•Prolonged facial mask ues in humans revealed adverse reactions like redness and dryness from excessive hydration.